Effects of urban heavy metal pollution on organic matter decomposition in Quercus ilex L. Woods - Cotrufo, M. F.; Santo, A. V. De; Alfani, Anna (Environmental Pollution, 1995)
Decomposition of oak (Quercus ilex) leaves containing different concentrations of Fe, Zn, Cu, Cr, Ni and Pb was measured in laboratory microcosms. The leaves were collected from a polluted site inside the city of Naples and from a control site away from the city. Soil was sampled from the upper A horizon (0-5 cm) at both sites and analyzed for respiration, microbial biomass and abundance of fungal mycelia. The soils from the two sites differed significantly in heavy metals concentrations. The accumulated mass loss reached an asymptotic value after four months both for the control and polluted litters. However, control and polluted litters significantly differed in accumulated mass loss, that was respectively 40 % and 29 % of the initial weight, after 10 months. Moreover decomposition rates appeared to be strongly influenced by metal contamination in the early stages, while in later stages, they did not differ significantly. Litter respiration appeared to be inhibited by metal contamination and showed pattern and rates consistent with those found for litter decomposition. Fungal mycelia were significantly less abundant both in litter and soil from the polluted site than from the con- trol site. Metabolic activity (both as soil respiration and degree of mineralization) was lower in the polluted soil. Soil respiration and amount of soil mycelia correlated negatively with soil Pb, Zn and Cr concentration.
Keywords: Fungal biomass (voyant9; Heavy metals; litter decomposition; pollution; Soil microbial biomass; Soil respiration